2006
DOI: 10.1111/j.1365-2249.2006.03276.x
|View full text |Cite
|
Sign up to set email alerts
|

Hyperactivity and reactivity of peripheral blood neutrophils in chronic periodontitis

Abstract: SummarySome evidence exists that peripheral neutrophils from patients with chronic periodontitis generate higher levels of reactive oxygen species (ROS) after Fcg-receptor stimulation than those from healthy controls. We hypothesized that peripheral neutrophils in periodontitis also show both hyper-reactivity to plaque organisms and hyperactivity in terms of baseline, unstimulated generation and release of ROS. Peripheral neutrophils from chronic periodontitis patients and age/sex/smoking-matched healthy contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
236
2
2

Year Published

2008
2008
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(261 citation statements)
references
References 54 publications
8
236
2
2
Order By: Relevance
“…Patient and control pairs were previously demonstrated to exhibit a high hyperresponsive differential (both hyperreactivity to Fc␥R-stimulation and baseline unstimulated hyperactivity) as determined by ECL (mean differential periodontitis vs health ϭ 13,897 RLU, range ϭ 8,300 -27,061 RLU), and these data have been published elsewhere (9,10). RNA samples were analyzed using human Affymetrix HG_U133A oligonucleotide arrays, as described at www.affymetrix.com/products/arrays/specific/hgu133.affx.…”
Section: Microarray Target Preparation Hybridization and Analysismentioning
confidence: 96%
See 3 more Smart Citations
“…Patient and control pairs were previously demonstrated to exhibit a high hyperresponsive differential (both hyperreactivity to Fc␥R-stimulation and baseline unstimulated hyperactivity) as determined by ECL (mean differential periodontitis vs health ϭ 13,897 RLU, range ϭ 8,300 -27,061 RLU), and these data have been published elsewhere (9,10). RNA samples were analyzed using human Affymetrix HG_U133A oligonucleotide arrays, as described at www.affymetrix.com/products/arrays/specific/hgu133.affx.…”
Section: Microarray Target Preparation Hybridization and Analysismentioning
confidence: 96%
“…The resultant collateral host tissue damage to the supporting periodontal tissues leads to progressive periodontitis and ultimately culminates in tooth loss (6). Several studies have demonstrated that PBN from chronic periodontitis patients are not only hyperreactive, in response to Fc␥R stimulation by periodontal pathogens, but also hyperactive, with respect to baseline unstimulated ROS production (7)(8)(9)(10). Although a host molecular defect in intracellular lipid signaling may explain peripheral neutrophil ROS hyperreactivity in the relatively rare form of the disease, localized aggressive periodontitis (11), this mechanism does not explain the patient predisposition observed in chronic periodontitis.…”
Section: P Eripheral Blood Neutrophils (Pbn)mentioning
confidence: 99%
See 2 more Smart Citations
“…22,23 Bone marrow PMNs from six WT and four Nrf2 À/À mice were incubated in a mixture of 3 mmol/L isoluminol and 6 U of horseradish peroxidase (Sigma-Aldrich) on preblocked 96-well plates, and stimulated with 10 À6 mol/L phorbol myristate acetate (Sigma-Aldrich). Relative light units (RU) were measured using a fluorescence spectrophotometer (Fisher Scientific, Waltham, MA).…”
Section: Extracellular Ros Measurementsmentioning
confidence: 99%